Pemulihan Psikologis Pasca Putus Cinta: Tinjauan Sistematik Mekanisme Kognitif dan Emosional - Indah Fitriani; Nida Hasanati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Romantic breakup is a common interpersonal stressor during emerging adulthood and is frequently associated with emotional distress. However, psychological recovery trajectories vary substantially across individuals, highlighting the role of internal psychological mechanisms. This systematic review aimed to synthesize empirical evidence on cognitive, emotional, and identity-based mechanisms involved in psychological recovery following romantic breakup among emerging adults. A systematic review was conducted in accordance with PRISMA guidelines. Quantitative and mixed-methods studies examining psychological mechanisms related to post-breakup adjustment in emerging adult populations were synthesized narratively. The synthesis identified rumination, emotion regulation, and self-concept clarity as key mechanisms associated with recovery trajectories. Rumination was linked to more persistent emotional distress, whereas adaptive emotion regulation strategies, particularly cognitive reappraisal and higher self-concept clarity were associated with more adaptive psychological adjustment. Psychological recovery following romantic breakup is a dynamic, multilayered adaptation process shaped by interacting cognitive, emotional, and identity-based mechanisms.